A first-principles study of the atomic layer deposition of ZnO on carboxyl functionalized carbon nanotubes: the role of water molecules. Issue 5 (28th January 2021) - Paez-Ornelas, J. I.; Fernández-Escamilla, H. N.; Borbón-Nuñez, H. A.; Tiznado, H.; Takeuchi, Noboru; Guerrero-Sánchez, J.
Abstract : Atomic description of ALD in systems that combine large surface area and high reactivity is key for selecting the right functional group to enhance the ligand-exchange reactions. Abstract : The formation of heterostructures that combine a large surface area with high surface activity has attracted the attention of the scientific community due to the unique properties and applications of these heterostructures. In this work, we describe – at the atomic level – the full reaction mechanisms involved in the atomic layer deposition of a hybrid ZnO/CNT inorganic structure. First, the pristine CNTs are chemically activated with a carboxylic acid, a process unique to carbon materials. Diethylzinc (DEZ) and water are used as gas-phase precursors to form ZnO. Our findings show that DEZ is physically adsorbed on the CNTs during the exposure of the first precursor. The ligand-exchange to generate chemisorbed ethyl zinc on the O side of the COOH group needs to overcome an energy barrier of 0.06 eV. This is a very small energy if compared to the values (0.5–0.6 eV) obtained in previous studies for OH functionalized surfaces. The height of the barrier is associated with the CO side, which mediates the H proton's exchange from the OH group to the C2 H5 ligand. Furthermore, upon exposure to the oxidizing agent (H2 O), ethyl zinc exchanges its last ligand as ethane, and it accepts a hydroxyl group through a self-limiting reaction with an energy barrier of 0.88 eV. Notice that the energy barrier of the second ligand-exchange is larger than of the first. We have also analyzed the effect in the saturation of the second precursor: as the quantity of water molecules increases, the long-range interactions tend to repel them. However, the energy barrier of the second ligand-exchange decreases from 1.53 eV to 0.88 eV for one and two water molecules, showing a clear dependence on the oxidizing agent. Non-covalent interactions are used as a tool to visualize the driving forces that take place during each partial reaction in real space. Our study points out the importance of using the right functionalization agent to achieve a controlled and conformal ALD growth at the initial steps of the formation of hybrid ZnO/CNT structures, as well as the role played by the oxidizing agent to lower the energy barrier on the second ALD step.